English Language Learners’ Attitude and Challenge Utilized M-Learning: Comparison Mobile Application Moodle and Google Classroom - Prasetya, Rizky Eka; Syarif, Achmad (ELT Worldwide: Journal of English Language Teaching, 2023)
Mobile learning became the alternative device and gadget in the online learning environment. Its implementation enabled English language learners to acquire and archive learning content regardless of their location or environment, ensuring that online learning is relevant. However, compact devices are restricted with various technicality challenges, and English lecturers and learners need their adaptation in university. The study aimed to measure and compare English language learners’ attitudes and challenge toward Moodle and Google Classroom mobile application (app). The study employed a quantitative descriptive approach applied to the survey research design cross-sectional. 149 English language learners were concerned as participants from South Jakarta Universities. The questioner findings revealed that the Google Classroom application had a moderately positive attitude toward mobile phones for language learning and teaching than Moodle Application. These findings suggest that the challenges of both platforms could be minimized by recognizing the comprehensive feature from both applications. The English language learners utilized and adopted to learn and develop their communicative capabilities in the Mobile-Assisted Language Learning (MALL) context. Its platforms could have the alternative device for conducting a comprehensive Learning Management System (LMS) rather than a personal computer or laptop interface. The characteristics of Moodle and Google Classroom mobile applications supported and enhanced both learners’ individual and social aspects of the online learning environment. The comparable parameters displayed Google Classroom application was more compatible with learning media than Moodle application. Nevertheless, the advance and complete feature would be accessed from Moodle application than Google Classroom.